(untitled) (Research, Society and Development, 2024)
There has been an increase in the cases of older individuals diagnosed with autism spectrum disorder (ASD), making it possible to consider the tools used for this diagnostic. The aim of this study is to present the first stages of the process of developing two new tools to help with this diagnostic process. A literature review was conducted to find measures built to assess ASD symptoms in adults and also in women. After that, specialists from neuropsychology and psychology evaluated the quality of the clarity and relevance of all items. Based on statistical analysis and comments, the items were revised, and two versions were created. Future developments of tools that help the diagnostic process must consider these gender differences, incorporating items that capture the more subtle and specific manifestations of ASD in women.